2022
DOI: 10.1007/s11060-022-04048-x
|View full text |Cite
|
Sign up to set email alerts
|

A consensus definition of supratotal resection for anatomically distinct primary glioblastoma: an AANS/CNS Section on Tumors survey of neurosurgical oncologists

Abstract: Supratotal resection (SpTR) of glioblastoma may be associated with improved survival, but published results have varied in part from lack of consensus on the de nition and appropriate use of SpTR. A previous small survey of neurosurgical oncologists with expertise performing SpTR found resection 1-2 cm beyond contrast enhancement was an acceptable de nition and glioblastoma involving the right frontal and bilateral anterior temporal lobes were considered most amenable to SpTR. The general neurosurgical oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…To mitigate this risk, volumetric analyses should be coordinated between participating centres, performed by semi-automatic or fully automatic segmentation software, double-checked by independent neuro-radiologists and accompanied by inter-rater variability measurements for full disclosure. Second, the AANS/CNS Section on Tumors published in 2022 the results of their survey investigating a consensus definition of supratotal resection 21. Approximately three-quarters of the respondents agreed that the right anterior temporal and right frontal would be the most suitable candidate locations for SMR.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this risk, volumetric analyses should be coordinated between participating centres, performed by semi-automatic or fully automatic segmentation software, double-checked by independent neuro-radiologists and accompanied by inter-rater variability measurements for full disclosure. Second, the AANS/CNS Section on Tumors published in 2022 the results of their survey investigating a consensus definition of supratotal resection 21. Approximately three-quarters of the respondents agreed that the right anterior temporal and right frontal would be the most suitable candidate locations for SMR.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, well-defined tumour margins seem to have little value for genotype prediction once a correlation with T2-FLAIR mismatch has been accounted for [ 24 ], but provided additional prognostic information within this tumour type. This may be particularly important when supratotal resection [ 29 ] is being considered. A trend towards earlier and more extensive surgical resection [ 30 - 32 ] and improving access to genetic sequencing methods arguably decreases the value of radiogenomics per se.…”
Section: Discussionmentioning
confidence: 99%
“…Supratotal resection was still defined differently by neurosurgical oncologists. Generally, resection beyond 1-2 cm for contrast-enhanced tumors or 1-2 cm beyond the boundary in Flair images for non-enhanced tumors could be considered acceptable supratotal resection (33). Evidence indicated that supratotal resection might improve EOR and prolong the progression-free as well as OS in glioma patients (34).…”
Section: Discussionmentioning
confidence: 99%